Effect of intralaryngeal muscle synkinesis on perception of voice handicap in patients with unilateral vocal fold paralysis. (20th January 2017) - Lin, R. Jun; Munin, Michael C.; Rosen, Clark A.; Smith, Libby J.
Abstract : Objectives/Hypothesis: Intralaryngeal muscle synkinesis associated with unilateral vocal fold paralysis (UVFP) is thought to preserve thyroarytenoid‐lateral cricoarytenoid muscle complex tone, resulting in a better voice despite the presence of vocal fold paralysis (VFP). This study compares voice handicap in patients with unilateral VFP (UVFP) with and without evidence of adductory synkinesis on laryngeal electromyography (LEMG). Study Design: Retrospective review of LEMG data and Voice Handicap Index‐10 (VHI‐10) scores of patients diagnosed with permanent UVFP. Methods: LEMG was performed within 1 to 6 months post onset of UVFP. Patients were stratified into two groups: 1) recurrent laryngeal nerve (RLN) neuropathy with synkinesis and 2) RLN neuropathy without synkinesis. Synkinesis was diagnosed when the sniff to phonation maximum amplitude ratio was ≥0.65. VHI‐10 scores at 6‐month follow‐up were recorded. Results: Four hundred forty‐nine patients with UVFP and who had an LEMG were reviewed. Eighty‐three patients met the inclusion criteria, with 16 in group 1 and 67 in group 2. There was no significant difference between the groups with regard to age, timing of LEMG from onset of VFP, number of patients undergoing temporary vocal fold injection or use of off‐label nimodipine. Average VHI‐10 scores at 6 months post onset of VFP were 14.4 ± 10.6 for patients with LEMG‐identified synkinesis (group 1) and 21.0 ± 10.1 for patients with no LEMG evidence of synkinesis (group 2). This was statistically significant ( P = .02). Conclusions: Patients with unilateral vocal fold paralysis and LEMG evidence of laryngeal synkinesis are more likely to have less perceived voice handicap than those without synkinesis. Level of evidence: 4. Laryngoscope, 127:1628–1632, 2017